EVALUATION OF OCCUPATIONAL HEALTH AND SAFETY KEY PERFORMANCE INDICATORS USING IN HEALTHCARE SECTOR - Korkusuz, Ammar Yasir; Inan, Umut Hulusi; Ozdemir, Yavuz; Basligil, Huseyin (YILDIZ TECHNICAL UNIV, 2018)
The importance of occupational health and safety is increasing day by day in Turkey; however the literature and researches are not sufficient in this field. There are still many issues that need to be investigated. Performance measurement is also one of the most important subjects in occupational health and safety field. After legislative, regulative changes and taken precautions, it is important to measure how the health and safety performance of the enterprises is affected by these changes. In this study, key performance indicators (KPIs), those are required for the measurement of occupational health and safety performance, are investigated. 15 KPIs, with measurable and concrete characteristics, are selected as a result of literature review and expert interviews. Later, with the help of 3 certified health and safety experts from healthcare sector, KPIs are ranked according to their importance by using Analytical Hierarchy Process, one of the multi criteria decision making methods. As a result, Fatal Accident Frequency Rate and Risks with High Importance are found the most important safety KPIs in healthcare sector. The main contribution of this study is to find measurable and objective key safety factors in healthcare sector and prioritize them by using the MCDM (Multiple Criteria Decision Making) technique, AHP. To the authors' knowledge this will be the first study in the literature that focuses on measurable KPIs and first study that prioritizes the key safety factors using AHP in healthcare sector.
Keywords: Analytic hierarchy process (AHP); key performance indicators (KPI); multi criteria decision making (MCDM); occupational health and safety (OHS); safety performance measurement; AHP; Engineering